IN VITRO CULTURE OF THREE ELITE CLONES OF JACKFRUIT - R. GAYATHRI; N. SATHYANARAYANA (The Bioscan, 2015)
Studies on in vitro culture in three elite clones of jackfruit were carried out during 2012-13 at PG Centre, UHS (Bagalkot), GKVK, Bengaluru. Three elite clones of jackfruit (Clone no. 1, 2 and 3) were identified from Doddaballapur, Bengaluru Rural District, Karnataka and used for the study. In the in vitro study, survival of shoot tips and nodal segments was highest (62.5%) in January with least fungal (14%) and bacterial contamination (23.5%) whereas least survival was recorded during September (20%). Shoot tips were suitable explants with highest shoot length (3.04 cm) over nodal segments (1.84 cm) with highest leaves (3.18). Chloramphenicol (60 mg/L) recorded least bacterial contamination (6.33%) and highest survival (80.60%) of the culture against basal medium (86.32% bacterial contamination with culture survival of 7.16%). BAP (2 mg/l) gave highest leaves (2.86) and longest shoots (3.08 cm) in vitro. Number of shoots was more in clone no. 2 (1.93) and highest shoot length (2.57 cm) was recorded in clone no. 3. From the study, it can be concluded that explants survival was highest when collected during January, chloramphenicol as antibiotic was effective in reducing bacterial contamination and BAP (2 mg/l) was effective for shoot proliferation of in vitro culture.